Morphological investigations of endomorphin-2 and spinoparabrachial projection neurons in the spinal dorsal horn of the rat - Yin, Jun-Bin; Lu, Ya-Cheng; Li, Fei; Zhang, Ting; Ding, Tan; Hu, Huai-Qiang; Chen, Ying-Biao; Guo, Hong-Wei; Kou, Zhen-Zhen; Zhang, Ming-Ming; Yuan, Jun; Chen, Tao; et al. (Frontiers in Neuroanatomy, 2022)
It has been proved that endomorphin-2 (EM2) produced obvious analgesic effects in the spinal dorsal horn (SDH), which existed in our human bodies with remarkable affinity and selectivity for the μ-opioid receptor (MOR). Our previous study has demonstrated that EM2 made synapses with the spinoparabrachial projection neurons (PNs) in the SDH and inhibited their activities by reducing presynaptic glutamate release. However, the morphological features of EM2 and the spinoparabrachial PNs in the SDH have not been completely investigated. Here, we examined the morphological features of EM2 and the spinoparabrachial PNs by using triple fluorescence and electron microscopic immunohistochemistry. EM2-immunoreactive (-ir) afferents directly contacted with the spinoparabrachial PNs in lamina I of the SDH. Immunoelectron microscopy (IEM) were used to confirm that these contacts were synaptic connections. It was also observed that EM2-ir axon terminals contacting with spinoparabrachial PNs in lamina I contained MOR, substance P (SP) and vesicular glutamate transporter 2 (VGLUT2). In lamina II, MOR-ir neurons were observed to receive direct contacts from EM2-ir varicosities. The synaptic connections among EM2, MOR, SP, VGLUT2, and the spinoparabrachial PNs were also confirmed by IEM. In sum, our results supply morphological evidences for the analgesic effects of EM2 on the spinoparabrachial PNs in the SDH.